Effect of the adding of the different Levels of selenium inorganic to the diet in productive and physiological performance of Ross 308 broilers - Rashid mousa, Ghassan (Journal of Kerbala for Agricultural Sciences, 2017)
The research was conducted to investigate the effect of different levels of inorganic selenium on the some productive and physiological traits of broilers .A total number of 400 one day old chicks (ross-308) were used in the experiments . chicks were randomly allocated in to 4 treatments, the First treatment fed an ordinary diet (control) , the second treatment Fed on a diet contained 20 mg / k100 kg selenium, the third treatment fed a diet contained 30 mg / 100 kg selenium and the fourth treatment 40 kg/ 100kg selenium, the experiment lasted 42 days . Results showed a significant effect (P<0.05) of selenium on body weights, the 4 th treatment surpassed on other treatments during the 6 th week as well as this treatment surpasses on other treatments in regard to the weight gains feed consumption was higher in treatments of selenium as compared with the control. No significant differences were noted in accumulative feed conversion rate (1-6 week) the fourth treatment surpassed on the second one as well as G.O.T and G.P.T enzymes during the 6th week.